The Application of Maslahah Mursalah in A Mediation Process Between Disputant Parties - Andika Catur Prastyo (Journal of Islamic Economic Laws, 2020)
The purpose of this study is to explore how is the mediation process in the Sragen District Court ta in Sharia economic disputes. It also seeks to determine the suitability of the mediation process in terms of the Maslahah Mursalah. This research is a field research with a qualitative approach. The data source of this study consists of primary data and secondary data. The location of this study is in Sragen District Court. Data collection techniques in this study were using documentation and interviews. This study shows that the mediation process in Islamic economic disputes is not much different from other disputes. This research also reveals that there is a non-compliance with the existing regulations, i.e that peace which is carried out by the parties occurs outside the court and there is no Peace Act. Based on this, it will lead to a different legal effect